Relación entre el dolor agudo post operatorio y las características anestésico - quirúrgica en pacientes sometidas a cesárea en Loreto 2021 - Rivera Vega de López, Nathaly Angélica María (2022)
The COVID-19 disease has increased exponentially, becoming a pandemic. Leaving a broad statistical record of morbidity and mortality, with shocking images and patients hospitalized through the corridors of the Loreto Regional Hospital. Therefore, prognostic parameters are needed, one of them being high basal levels of D-dimer, however, its predictive value is limited for thrombosis, so dynamic changes must be taken into account. The present work aims to describe the dynamic changes of coagulation parameters during hospitalization, as well as their association with the clinical results of hospitalized patients, in addition to evaluating the prevalence of high values of D-dimer in patients with pneumonia. by COVID-19. The intention of this descriptive cross-sectional observational research project includes as a population hospitalized patients over 18 years of age with a confirmed diagnosis of COVID-19 and who have at least one D-dimer test on admission, during the months of May to November 2020. And as an exclusion criterion for those who have never had a D-dimer test. With this information that will be obtained, it is intended to know the high prognostic value of the dynamic changes of D-Dimer in patients with COVID- 19 at the time of evaluation.